EVALUATION OF DEPRESSION AND ANXIETY AMONG THE MEDICAL STUDENTS OF PUMHSW NAWABSHAH. - Arslan Ahmer1, TahseenAhmed2, Moti Ram Bhatia3, Durr-e-Shahwar Malik4, Fahad Jibran Siyal5, Saeed Ahmed Lakho6, Jabbar Abbas7. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objectives: To evaluate the prevalence of anxiety and depression among medical students of PUMHSWNawabshah and factors associated with mental retardation of students. Methodology: Across-sectional study was conducted atPUMHSW Nawabshah for the period of 07 monthsfrom August 2019 to February 2020. Total 319 study subjects had participated belonging to various medical disciplines. A questionnaire was given to them and all the participants were guided about filling of that questionnaire. Questions regarding the mental approach of students, level of anxiety & depression and factors associated with psychiatry problems were asked. Different measuring scales were used to evaluate the frequency of depression and anxiety. Chi-Square test was applied to evaluate the research data. Results: The students with various age groups from 21 to 30 with each type of gender and total 319 study subjects were included. Among all 207 were females and 112 were males. Frequency of anxiety and depression was more common in females because of socio economic values and educational burden was the route cause for creating depression and anxiety. Conclusion: One-third portion of total study subjects were found with anxiety and depression because of their academic burden and non-academic factors such as economy of students, psychiatry issues, residential problems and even sudden loss of family member or close friend can enhance the prevalence of depression & anxiety.y.